Evaluasi Pemahaman Taruna Pelayaran Mengenai Prinsip dan Ketentuan UNCLOS 1982 dalam Hukum Laut Internasional - Femmy Asdiana Femmy; Natriya Faisal Rachman; Elly Kusumawati; Muhammad Razka; Fausta Okta Rakha Putra (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to evaluate the level of understanding of maritime cadets regarding the basic principles and provisions of the 1982 United Nations Convention on the Law of the Sea (UNCLOS), which forms the basis of international maritime law. The primary focus includes understanding maritime boundaries, exclusive economic zones (EEZs), the right of innocent passage, and the obligations of coastal states and flag states. The study employed a quantitative descriptive approach with a questionnaire-based survey. A purposive sample of 100 final-year cadets at a maritime polytechnic was selected. Data were analyzed using descriptive statistics to measure understanding, supplemented by limited interviews to deepen the findings. The results indicate that the average cadet's understanding is moderate (62.5%), with significant weaknesses in aspects of maritime dispute resolution and the right of passage through archipelagic waters. The best understanding is found in the definition of the EEZ and territorial sea boundaries. The study recommends increasing the integration of real-life case studies and legal simulations into the curriculum to strengthen cadets' maritime law literacy before entering the world of international maritime work.